2022
DOI: 10.3389/fenrg.2021.838307
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Role of Green Fiscal Policies With Energy Prices Volatility and Energy Efficiency: Presenting a COVID-19 Perspective

Abstract: Energy and other related sectors are changing in China. This study attempted to estimate the energy product price volatility with energy efficiency during COVID-19 with the role of green fiscal policies. For this, we applied unit-root tests, ADCC-GARCH, and CO-GARCH techniques to infer the study findings. The results showed that energy price volatility was significantly connected until 2018. More so, the green fiscal policies were significantly connected between energy product price volatility and energy effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Additionally, Chang et al [58] analyze the interplay between subsidies, tax rebates, and research and development (R&D) policies and their impact on the market valuation of Chinese renewable energy companies. The study presented a noteworthy inverted U-shaped correlation between government subsidies and market value, particularly when combined with R&D investment.…”
Section: Fiscal Policy and Renewable Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Chang et al [58] analyze the interplay between subsidies, tax rebates, and research and development (R&D) policies and their impact on the market valuation of Chinese renewable energy companies. The study presented a noteworthy inverted U-shaped correlation between government subsidies and market value, particularly when combined with R&D investment.…”
Section: Fiscal Policy and Renewable Energy Consumptionmentioning
confidence: 99%
“…Additionally, the studies of Khan, et al [95], Zhang, et al [96], and ref. [58] probe the role of natural resources in the inclusion of clean energy.…”
Section: Natural Resources and Clean Energy/re Consumptionmentioning
confidence: 99%
“…From the table above, it could be reported that the degrees of correlation that exists between different pairs of the regressors are so low that the highest correlation in the table is 0.652. This implies that the subsequent regression will be freed from the problem of multicollinearity as reinforced by the submission of [ 38 ] claiming that it is only the pair of regressors with correlation of 0.9 has capacity cause multcollienarity in a model.…”
Section: Resultsmentioning
confidence: 99%
“…Transformation of equation (2) into a panel econometrics model results into the following equation. in response to the pre-estimation analysis of the employed data that confirms the existence of mixture of I (0) and I (1) among the variables, this study estimated a panel autoregressive distributed lag model, following the submission of [ [35] , [36] , [37] , [38] , [39] ]. The ARDL model in panel form is stated as follows; …”
Section: Methodsmentioning
confidence: 99%
“…This has led to the adoption of distributed production resources in order to establish a smart and eco-friendly network (Jamil et al, 2022;Almalki et al, 2023). The use of fossil fuels to meet this level of demand without proper energy management will result in the depletion, if not the extinction, of these natural resources (Yin et al, 2022;Nikbakht Naserabad et al, 2023). As a result, today's humanity is attempting to use renewable resources to help meet this massive and ever-increasing demand (Pachar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%